Tuberculosis household contact tracing in children: axes of inequality, Barcelona 2003–2022 - Prieto-García, Raquel; Millet, Joan Pau; Soriano-Arandes, Antonio; Espiau, María; Broto, Claudia; Ronda, Mar; López, Núria; Noguera-Julian, Antoni; Masdeu Corcoll, Eva; Domingo Jimenez, Cristina; Ros Samsó, Miriam; Marcos Arroita, Maria Isabel; et al. (Frontiers in Public Health, 2025)
Children under 15 years of age living in the household of a tuberculosis case constitute a very vulnerable group to tuberculosis infection (TBI). The objective of this study was to determine the prevalence of TBI and the risk factors associated with presenting TBI in this group, considering sex, age, and migratory status as axes of inequality. A population-based, analytical, cross-sectional observational study was carried out in the city of Barcelona in the period 2003–2022. The study population was household contacts under 15 years of age with index cases of pulmonary TB reported to the Barcelona Public Health Agency in the period 2003–2022. The analyses were performed using Generalized Estimating Equations (GEE) to predict the risk of TBI among these cohabiting contacts and were stratified considering the inequality axes of sex and migratory status. A total of 1084 contacts under 15 years of age were studied from 693 cases of tuberculosis. TBI prevalence among contacts was 24.5%. The factors associated with the presence of TBI in the contacts were having a smear positive in the index case, being older than 5 years in the contacts ([5,10], [10–15]) and the case and the contact being migrants; smear positive when the index case was native women and being from a municipal district with a lower incidence of tuberculosis when the index case was native women and the men. The results of the study confirm the importance of carrying out contact tracing and follow-up of household children, especially if the index case is smear positive. Contact tracing should be carried out as soon as possible to assess the prescription of primary chemoprophylaxis and TBI treatment to avoid rapid TB progression in children.